Direct Brain Targeted Nanostructured Lipid Carriers for Sustained Release of Schizophrenic Drug: Formulation, Characterization and Pharmacokinetic Studies - Sivadasu, Praveen; Gowda, Devagowda Vishakante; Subramani, Nithin Kundachira; Vishweshwaraiah, Bhavya Malgur; Shivanna, Sachhidananda; Hatna, Siddaramaiah (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Systemic drug delivery in schizophrenia is a major challenge, owing to the Blood-brain Barrier (BBB) and P-glycoprotein related effects. Consequently, herein an attempt is made to systemically deliver the most desirable schizophrenia drug, Quetiapine Fumarate (QF) via non-invasive intranasal route using Nanostructured Lipid Carrier (NLC) approach. Materials and Methods: The desired QF loaded NLCs were developed using central composite statistical design and the developed formulations were monitored for improving QF bioavailability and their brain targeting efficacies. Results: The optimized formulation displayed a 2-fold increase (compared to virgin QF) in ex-vivo nasal diffusion at the 6th hr, with no sign of structural damage (upon histopathological examinations). While, QF blood-brain ratio showed 10-fold increase for NLCs administered through nasal route (in comparison to intravenous route), thereby supporting prolonged retention of QF at the site of action. Similarly, the concentration of QF (in the brain) delivered via nasal route exhibited 4-fold increment at all-time points thereby supporting a potential nose to brain transport and effective bypassing of BBB. Conclusion: The results obtained infers that non-invasive intranasal route can be used as a potential alternative to conventional treatment options towards efficient management of schizophrenia.
Keywords: Nanostructured lipid carriers; Quetiapine fumarate; Schizophrenia; Brain; Targeting; Intranasal route